2019
DOI: 10.1111/phpr.12624
|View full text |Cite
|
Sign up to set email alerts
|

Empathetic Understanding and Deliberative Democracy

Abstract: Epistemic democracy is standardly characterized in terms of "aiming at truth". This presupposes a veritistic conception of epistemic value, according to which truth is the fundamental epistemic goal. I will raise an objection to the standard (veritistic) account of epistemic democracy, focusing specifically on deliberative democracy. I then propose a version of deliberative democracy that is grounded in non-veritistic epistemic goals. In particular, I argue that deliberation is valuable because it facilitates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 67 publications
(97 reference statements)
0
9
0
1
Order By: Relevance
“…A possible example from the intellectual realm involves the qualities of a group involved in fostering and cultivating mutual empathetic understanding. Michael Hannon (2020) argues that democratic deliberation might be good for an empathetic understanding of other people. Understanding others, he writes, requires 'that we be willing to listen to them.…”
Section: Emergencementioning
confidence: 99%
“…A possible example from the intellectual realm involves the qualities of a group involved in fostering and cultivating mutual empathetic understanding. Michael Hannon (2020) argues that democratic deliberation might be good for an empathetic understanding of other people. Understanding others, he writes, requires 'that we be willing to listen to them.…”
Section: Emergencementioning
confidence: 99%
“…Desde distintos puntos de vista, se ha considerado que la situación de deliberación democrática incentiva a los interlocutores a tomar en consideración, sinceramente, los intereses comunes y la justicia (Elster, 2003). Por tanto, se cree que el proceso democrático tiende a fortalecer la autonomía, la racionalidad, el entusiasmo y la moralidad de los participantes (Hannon, 2020). Al mismo tiempo, la clara determinación de la posición del gobierno democrático como punto medio entre el pueblo y el pueblo mismo, da lugar a un círculo virtuoso, el cual tiende a mejorar también la calidad de la legislación y la política pública.…”
Section: Sintesis: Concepto Tridimensionalunclassified
“…Some have suggested that the solution to the problem of epistemic identity involves imagining someone else's identity (Hannon 2020). Others have suggested that we should activate a superordinate identity ( Van Bavel and Pereira 2018).…”
Section: If You Can't Beat Epistemic Identity Embrace Itmentioning
confidence: 99%